SELF-EFFICACY DAN KECEMASAN TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS: SYSTEMATIC LITERATURE REVIEW - Nur Azhari, Ratu; Pujiastuti, Heni; Nandang Mustafa, Ade (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Cognitive success in mathematics learning at the Vocational High School (SMP) level is often hampered by complex psychological variables, particularly during the post-pandemic curriculum transition. This research is crucial because low conceptual understanding often stems from affective factors that receive insufficient attention in classroom instruction. The purpose of this study was to analyze the profile of mathematical conceptual understanding from the perspective of self-efficacy levels, identify the impact of math anxiety on cognitive performance, and formulate effective learning strategies. The research method used was a Systematic Literature Review (SLR) using the PRISMA guide. Data were collected from Google Scholar, the Garuda Portal, and the SINTA database using accredited article inclusion criteria from 2020 to 2025. Qualitative analysis was conducted on 10 reference articles covering cognitive, affective, and physiological indicators. The results showed that self-efficacy was a key predictor, indicating that students with low efficacy tend to be stuck at the pre-structural level in the SOLO taxonomy. Meanwhile, math anxiety has been shown to reduce working memory capacity, which manifests in cognitive and physiological disturbances during exams. The main findings indicate that strengthening self-efficacy can significantly mediate the reduction of math anxiety. The results of this study emphasize the importance of integrating educational psychology into learning. The proposed strategic recommendation is the implementation of a hybrid learning model supported by TPACK-based media and augmented reality (AR) to facilitate the visualization of abstract concepts while creating a supportive learning experience for vocational high school students.